Disaster Response System Dynamic Assessment Model Based on Questionnaire Investigation: A Case Study of Nuclear Accident Preparedness Education - Ching-Yi Wu; Yi-Lung Yeh (Engineering Proceedings)
Based on the results of the nuclear accident response education questionnaire, we use system dynamics to develop a nuclear accident response education effectiveness evaluation model. A questionnaire survey was conducted for the pre- and post-tests of the course to understand course effectiveness and explore the interactive relationship between factors. The system dynamics is used to develop a nuclear accident response education effectiveness evaluation model. Age and education are significantly related to education and training experience (number of times), and the age, occupation, and education level are significantly related to individuals’ experience (number of times) of participating in a nuclear accident evacuation exercise. In the workshop courses, the public’s awareness of self-protection against nuclear accidents was significantly improved. Experience in educational training was significantly related to evacuation exercises. Individuals’ age and experience of participating in education and training can be used to predict their willingness to participate in evacuation exercises. Using systems thinking and analysis, an evaluation model for nuclear incident response education effectiveness is constructed as a reference for evaluating effectiveness. The designed education and training courses can increase public participation in nuclear accident response education and strengthen the cognitive benefits of response protection.